2017
DOI: 10.1186/s12916-017-0817-5
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical evaluation of a TEX101 protein ELISA test for the differential diagnosis of male infertility

Abstract: BackgroundTEX101 is a cell membrane protein exclusively expressed by testicular germ cells and shed into seminal plasma. We previously verified human TEX101 as a biomarker for the differential diagnosis of azoospermia, and developed a first-of-its-kind TEX101 ELISA. To demonstrate the clinical utility of TEX101, in this work we aimed at evaluating ELISA performance in a large population of fertile, subfertile, and infertile men.MethodsMass spectrometry, size-exclusion chromatography, ultracentrifugation, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(83 citation statements)
references
References 41 publications
3
77
0
3
Order By: Relevance
“…1B), and were subsequently expanded in serum-free media and purified using protein G columns. We showed previously that the commercial polyclonal antibody ab69522 could capture native TEX101 (28,35). Immunocapture-SRM results revealed that our monoclonal anti-TEX101 antibodies possessed higher affinity for native TEX101 than ab69522 (Fig.…”
Section: Production Of Tex101 Protein and Mouse Monoclonal Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…1B), and were subsequently expanded in serum-free media and purified using protein G columns. We showed previously that the commercial polyclonal antibody ab69522 could capture native TEX101 (28,35). Immunocapture-SRM results revealed that our monoclonal anti-TEX101 antibodies possessed higher affinity for native TEX101 than ab69522 (Fig.…”
Section: Production Of Tex101 Protein and Mouse Monoclonal Antibodiesmentioning
confidence: 99%
“…In this study, we focused on the testis-specific protein TEX101, which we previously discovered and validated as a biomarker of male infertility (27)(28)(29)(30)(31). Similarly to other testisspecific proteins involved in PPIs, TEX101 is exclusively expressed on the surface of testicular germ cells (32) and was suggested to be a cell-surface chaperone involved in trafficking and maturation of numerous cell surface proteins essential for fertilization in mice (7,33).…”
Section: Introductionmentioning
confidence: 99%
“…http://dx.doi.org/10.1101/120873 doi: bioRxiv preprint first posted online Mar. 26, 2017; Our work resulted in first-of-a-kind SP-based biomarkers for the differential diagnosis of male infertility [23][24][25] . Success with male infertility biomarkers motivated us to apply a similar strategy to prostate cancer biomarkers.…”
Section: Cc-by-nc-nd 40 International License Peer-reviewed) Is the mentioning
confidence: 99%
“…We also found that unlike mouse antibody, sheep antibody could barely capture rhTGM4. We then coated ELISA plates with 300 ng/well of either sheep or mouse antibodies, incubated with either rhTGM4 (0, 5, 20 and 100 ng/mL) or endogenous TGM4 in SP (0, 5, 20 and 100 ng/mL) and detected with biotinylated sheep or mouse antibodies and standard time-resolved fluorescence ELISA format 25 .…”
Section: Development Of Tgm4 Elisamentioning
confidence: 99%
See 1 more Smart Citation